Surgical Management of Soft Tissue Sarcoma - Muhammad Mukhtar Khan, S H Waqar, Raja Amjad Mahmood, M A Zahid (Journal of Rawalpindi Medical College, 2018)
Background: To study the management pattern of soft tissue sarcomas in a tertiary care setting Methods: In this descriptive study patients who were operated for soft tissue masses were included. Intra-operative findings, procedure details and postoperative orders were recorded. Postoperative chemo-radiotherapy records were reviewed and recorded. Depth of the tumour was grouped as deeper or superficial than 5 cm. The follow up records were accessed from the outpatient department and any surgical complications were recorded up to three years.Staging was done using clinical and radiological criteria taking into account the histological grade,tumour size , depth, local lymph node invasion and metastasis.Surgical procedure for removal of STS are wide local excision (WLE), intralesional excision (IE) or tumor debulking, marginal excision (ME) and radical excision (RE). Results: Sixty eight patients with mean age of 43.0 ± 17.258 SD were diagnosed as cases of soft tissue sarcomas. Male to female ratio was 3.25:1.The most common histopathological variety was malignant fibrous histiocytoma (35.3%) , followed by Rhabdomyosarcoma(30%). Most common involved site was lower limbs (35.3%).Wide local excision was performed in majority (82.4%) . Most common postop complication was wound infection (10.3%) Conclusion: Clinicians must be agile about the nature of these tumours and their referral to a specialist surgeon for further management. Prompt diagnosis, accurate investigations and early intervention will benefit the patients and help us understand this disease entity.